Integrating soil test-based fertilizers and biofertilizers to boost groundnut (Arachis hypogaea) productivity on sandy clay soils in semi-arid tropics - PAVAN, B.; LAKSHMAN, K.; REKHA, M. SREE; NASEERUDDIN, R.; SREEKANTH, B.; SHARMA, R. P. (Journal of Soil and Water Conservation, 2025)
A field experiment was conducted on sandy clay soil at the Agricultural College Farm, Bapatla, during the 2019 kharif season to study the response of groundnut to various fertilizer levels and liquid biofertilizers. The experiment included eleven treatments: a control, 100% soil test-based fertilizer recommendation (STBR), and three fertilizer levels (100%, 75%, and 50% of STBR) combined with either conventional carrier-based biofertilizers (Rhizobium and phosphorus-solubilizing biofertilizer), liquidbased biofertilizers (Rhizobium and PSB), or a liquid NPK microbial biofertilizer consortium, arranged in a randomized block design with three replications. Results showed that the highest number of pods per plant (18.07) and a 60% increase in pod yield (2921 kg ha-1) were achieved with 100% STBR + liquid NPK microbial biofertilizer consortium, compared to the control (1830 kg ha-1), and were comparable to the 75% STBR + biofertilizer application. This study highlights the benefits of soil test-based fertilizer application in combination with biofertilizers for enhancing groundnut growth and yield.